Dating violence victimization across the teen years: Abuse frequency, number of abusive partners, and age at first occurrence - Bonomi Amy E; Anderson Melissa L; Nemeth Julianna; Bartle-Haring Suzanne; Buettner Cynthia; Schipper Deborah (BMC, 2012)
Abstract Background Prior longitudinal studies have shown high cumulative dating violence exposure rates among U.S adolescents, with 36 percent of males and 44 percent to 88 percent of females experiencing victimization across adolescence/young adulthood. Despite promising information characterizing adolescents' dating violence experiences longitudinally, prior studies tended to concentrate on physical and sexual types of violence only, and did not report information on the number of times dating violence was experienced across multiple abusive partners. We used a method similar to the timeline follow-back interview to query adolescents about dating violence victimization from age 13 to 19-including dating violence types (physical, sexual, and psychological), frequency, age at first occurrence, and number of abusive partners. Methods A total of 730 subjects were randomly sampled from university registrar records and invited to complete an online survey, which utilized methods similar to the timeline follow-back interview, to retrospectively assess relationship histories and dating violence victimization from age 13 to 19 (eight questions adapted from widely-used surveys covering physical, sexual, and psychological abuse). Then, for each dating violence type, we asked about the number of occurrences, number of abusive partners, and age at first occurrence. Of 341 subjects who completed the survey, we included 297 (64 percent females; 36 percent males) who had a dating partner from age 13 to 19. Results Fully 64.7 percent of females and 61.7 percent of males reported dating violence victimization between age 13 and 19, with most experiencing multiple occurrences. More than one-third of abused females had two or more abusive partners: controlling behavior (35.6 percent); put downs/name calling (37.0); pressured sex (42.9); insults (44.3); slapped/hit (50.0); and threats (62.5). Males also had two or more abusive partners, as follows: controlling behavior (42.1 percent); insults (51.2); put downs (53.3); threats (55.6); and unwanted calls/texts/visits (60.7). Among abused females, 44.7 percent first experienced controlling behavior between age 13 and 15, whereas the majority (62.5 percent) first experienced pressured sex between age 16 and 17. Among males, for most abuse types, 16 percent to 30 percent of victimization began before age 15. Conclusions Our study adds information to a substantial, but still growing, body of literature about dating violence frequency, age of occurrence, and number of abusive partners among adolescents.